Peranan Pengelolaan Keuangan Badan Usaha Milik Kampung dalam Meningkatkan Perekonomian Masyarakat Kampung Paya Kulbi - Sugama, Yoga; Yahya, M.; Safwandi (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
Village development must also be pursued in order to improve the economy towards the quality of life and welfare of the community. One way to accelerate the economic growth of the Village Community is to establish a Village-Owned Enterprise (BUMK). Village-Owned Enterprises (BUMK) have a very important financial management role in the form of Village Funds. The purpose of this study was to determine the role of Financial Management of Village-Owned Enterprises, factors that influence Village-Owned Enterprises and obstacles to Village-Owned Enterprises (BUMK) in improving the economy of Paya Kulbi Village, Karang Baru District. This research method uses a Descriptive Qualitative Approach Research type. Research data collected based on the results of observations, interviews and documentation. Data Analysis Tools used are Data Reduction, Data Presentation and Conclusion Drawing. The results of this study indicate that the financial management of the Baguna Village-Owned Business Entity goes through the Planning stage, which is carried out through the building planning deliberation meeting according to the Basic Budget. Implementation is carried out by making proposals until business activities run. Administration is carried out by writing and recording financial reports in the daily cash book. Financial reporting accountability is carried out twice a year. Supervision is carried out in the form of guidance from the District Office and Datok Penghulu